2011
DOI: 10.1089/cap.2010.0123
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Trial of Risperidone in Children and Adolescents with Severe Mood Dysregulation

Abstract: Risperidone was effective in reducing irritability in SMD youth. To the best of our knowledge, this is the first psychopharmacological trial in this group of patients with positive results. Further randomized, controlled studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…A small study of lithium (n=14) vs. placebo (n=11) was ineffective for treatment of SMD 47 , while a small (n=21) open-label trial showed that risperidone reduced irritability in SMD 48 . The diagnostic stability of DMDD is not known in youth at risk for BD, and optimal treatment approaches may differ in this population.…”
Section: Discussionmentioning
confidence: 99%
“…A small study of lithium (n=14) vs. placebo (n=11) was ineffective for treatment of SMD 47 , while a small (n=21) open-label trial showed that risperidone reduced irritability in SMD 48 . The diagnostic stability of DMDD is not known in youth at risk for BD, and optimal treatment approaches may differ in this population.…”
Section: Discussionmentioning
confidence: 99%
“…49 An open label trial using low doses (mean 1.2±0.5 mg) of risperidone in children and adolescents with SMD showed significant reductions in irritability scores (Aberrant Behavior Checklist-Irritability at baseline 25.89, standard error [SE] 2.7, and at week 8 11.28, SE 3.06, p < 0.001). 50 Risperidone was also effective in reducing duration of rage outbursts in inpatient settings (baseline 44±20 min, last dose 25±12 min). 51 Indeed, risperidone is FDA approved for the treatment of irritability in patients with autism spectrum disorders, although irritability in autism may not be the same as the one found in typically developing children.…”
Section: Therapeutic Strategies For Chronic Irritabilitymentioning
confidence: 96%
“…However, we are only beginning to systematically evaluate the efficacy of this practice. An open-label trial of risperidone (mean dose = 1.28 mg) in youth with SMD showed significant reduction in irritability scores 70. In a randomized, controlled trial, augmenting psychostimulant and parent training with risperidone versus placebo in children with ADHD and severe aggression led to moderate but variable improvement in aggressive behaviors over 9 weeks.…”
Section: Treatmentmentioning
confidence: 99%